Policy, practice, and parenthood: a study of teacher mothers. Issue 1 (2nd January 2023) - Hermann, Mary A.; Gorlewski, Julie; Brookover, Dana; Walsh, Robyn; Kozachuk, Lindsay; Deitz, Michael; Ciminelli, Elizabeth
ABSTRACT: This phenomenological study extends the current research on working mothers to teacher mothers. Themes highlighted include work/life enrichment, support for motherhood role, challenge to find balance, challenging cultural norms, financial challenges, and strategies for managing multiple roles. Findings reveal and highlight challenges and opportunities that exist at the intersection of the field of education and motherhood. Also provided are suggestions for advocacy efforts for norms and policies that support teacher mothers. Implications of this work are particularly relevant in the contemporary era, wherein the roles of motherhood and teacher are intensified by the shift to online learning as a result of the pandemic.